Characterization of a mechanochemically activated titanium-hematite mixture: Mössbauer spectroscopy study - Cristobal, Adrian Alberto (2009)
Mechanochemical processes involving reactions between metals and crystalline oxides are of interest because of their potential technological applications in structural, magnetic or electric materials. In addition they can contribute to the understanding of the natural occurring processes that lead to the formation of minerals and soils. The controlled studies of how the distribution of cations in the titanomagnetites takes place can help toward building a model for the nature of their magnetism and, since they are the primary carriers of rock and soil magnetism, are therefore intensively investigated in many experimental and theoretical studies. In behalf of a better comprehension of the thermal, physical-chemical, magnetic and hyperfine behavior, we have considered a titanium and hematite mixture, with molar ratio Ti:Fe2O3 of 1:2, mechanochemically activated during different activation times. We have studied the development of new phases by X-ray diffraction, scanning electron microscopy and Mössbauer spectroscopy. The evolution from the starting materials affected by different milling times and subsequent annealing shows that Ti reduces the Fe ions in the Fe2O3 lattice, partly to Fe2+ and partly to metallic Fe. © 2009 Elsevier B.V. All rights reserved.